A self-powered brain multi-perception receptor for sensory-substitution application. (February 2018) - Fu, Yongming; Zhang, Mengyang; Dai, Yitong; Zeng, Hui; Sun, Cong; Han, Yechao; Xing, Lili; Wang, Shuai; Xue, Xinyu; Zhan, Yang; Zhang, Yan
Abstract: The artificial sensory-substitution system can work like real human sensory tissue and participate in the perception of sensory-handicap patient. The power-supply unit is key factor for its wearable, low-cost and long-term application. Here, a new self-powered multi-perception electronic-skin has been presented as brain sensory receptor for sensory substitution of tactility, audition, olfaction, gustation and vision. The device directly outputs the triboelectric sensory signal into brain using human motion energy without external electricity power or battery, and actively involves in multi-perceptions. The sensing unit arrays act as both the power source and brain sensory receptor for tracking force trace, hearing words, smelling odor, tasting beverage and recognizing image. The mechanism can be attributed to the coupling of triboelectrification and surface effect. The device connecting to mouse brain at primary somatosensory barrel cortex can mimic the mouse perception and drive the mouse activities. This new approach can be applied to fabricating new self-powered sensory-substitution systems and multi-perception brain sensory receptor. Graphical abstract: Self-powered multi-perception electronic-skin as brain sensory receptor for sensory substitution has been presented. The sensor unit arrays can continuously mimic diverse perceptions and transmit the code signals to brain, which can involve in mouse perception and drive mouse behavioral responses. Highlights: A self-powered electronic-skin is developed as brain multi-perception receptor. The device can harvest human-motion energy and output the signal into brain. The triboelectric signals act as both power source and sensory information. The mechanism can be attributed to triboelectric-surface coupling effect. The device is connected to mouse brain to in vivo control mouse activity.